1993
DOI: 10.1007/bf00021423
|View full text |Cite
|
Sign up to set email alerts
|

Plant viral leaders influence expression of a reporter gene in tobacco

Abstract: In order to optimise expression of a foreign protein in transgenic plants we investigated the potential benefits of including a viral untranslated leader sequence within a plant transformation vector. A variety of 5 leaders, including the tobacco mosaic virus (TMV) leader sequence and 31 nucleotides of the cauliflower mosaic virus (CaMV) 35S RNA leader, were compared. Viral leader constructs employing the 35S promoter and the reporter beta-glucuronidase (GUS) were tested by electroporation into tobacco mesophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 43 publications
(72 reference statements)
1
10
1
Order By: Relevance
“…The latter could be important for greater message stability or translation efficiency. The first 60 nucleotides of the CaMV leader (from + 1 to the first ATG) stimulate expression of a downstream gene by about 2-fold [14,17]. Similar effect has been reported for the untranslated leader of the rice tungro bacilliform virus promoter [11 ].…”
Section: Discussionsupporting
confidence: 57%
“…The latter could be important for greater message stability or translation efficiency. The first 60 nucleotides of the CaMV leader (from + 1 to the first ATG) stimulate expression of a downstream gene by about 2-fold [14,17]. Similar effect has been reported for the untranslated leader of the rice tungro bacilliform virus promoter [11 ].…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies have shown that activity of the CaMV 35S promoter was enhanced two- to threefold with the addition of the translational enhancer TMV omega element in stably transformed Arabidopsis thaliana plants [29] as well as in transiently transformed tobacco protoplasts [30]. …”
Section: Resultsmentioning
confidence: 99%
“…The PEAMT coding sequence was amplified by PCR, using Pfu polymerase (Stratagene) with the forward primer 5Ј-AGCTTCTAGAT T T T TACA ACA AT TACCA ACA ACA-ACA A ACA ACA A ACA ACAT TACA AT TACTAT T TAC-A AT TACA A A A ATGGCCGCT TCAGCTATGG-3Ј, the reverse primer 5Ј-ACGTGGATCCTCACAT T T TCT TG-GCAATG-3Ј, and pREP3-PEAMT (12) as template. The forward primer includes the tobacco mosaic virus ⍀ sequence (18) and alters the sequence context of the start codon as described (19). The reaction product was ligated to pFMV as an XbaI͞ BamHI fragment to yield pFMV-PEAMT.…”
Section: Methodsmentioning
confidence: 99%
“…The spinach PEAMT coding sequence (12), preceded by the ⍀ translational enhancer (18) and the figwort mosaic virus 34S promoter (17), was cloned into an Agrobacterium binary vector with a glyphosate-resistance marker. This construct was used to transform tobacco plants that were coexpressing spinach CMO (19) and beet BADH (20) and so contained a transgenic GlyBet pathway in their chloroplasts.…”
Section: Peamt Overexpression Enhances Cho Levelsmentioning
confidence: 99%